Peningkatan Pemahaman dan Praktik Pengelolaan Limbah Cair pada Bengkel May Car Bodyworks melalui Kegiatan Sosialisasi dan Pendampingan - Ridho Hans Gurning; Abdul Wahid Arohman; Adinda Rahmah Shalihah; Moch. Fahmi Azizi (Sewagati, 2026)
This community service activity aimed to improve the understanding and practices of wastewater management at May Car Bodyworks Workshop through socialization and technical assistance. The initial problems faced by the partner included limited knowledge of the characteristics of workshop wastewater, its potential environmental pollution impacts, and the obligations related to wastewater management in accordance with existing regulations. The activity methods consisted of problem identification, interactive socialization, technical assistance, and simulation of the implementation of a simple wastewater treatment system in the form of infiltration wells and preliminary filtration. The materials were delivered in an applicative and contextual manner to ensure suitability with the operational conditions of small- and medium-scale workshops. The results indicated an improvement in the understanding of workshop owners and employees regarding the types and hazards of wastewater, the importance of separating oily wastewater, and the implementation of preliminary treatment prior to disposal. In addition, a commitment was established among the partners to adopt more environmentally friendly and sustainable work practices. This activity contributed positively to environmental protection efforts, increased awareness among business actors, and supported the implementation of wastewater management policies at the workshop level. The participatory approach employed also encouraged behavioral change, enhanced social responsibility, and demonstrated potential as a simple wastewater management model for similar workshops in Indonesia.